Effects of Extrusion Pretreatment Parameters on Sweet Sorghum Bagasse Enzymatic Hydrolysis and Its Subsequent Conversion into Bioethanol. (19th March 2015) - Heredia-Olea, Erick; Pérez-Carrillo, Esther; Montoya-Chiw, Manuel; Serna-Saldívar, Sergio O.
Abstract : Second-generation bioethanol production from sweet sorghum bagasse first extruded at different conditions and then treated with cell wall degrading enzymes and fermented with I. orientalis was determined. The twin extruder parameters tested were barrel temperature, screws speed, and feedstock moisture content using surface response methodology. The best extrusion conditions were 100°C, 200 rpm, and 30% conditioning moisture content. This nonchemical and continuous pretreatment did not generate inhibitory compounds. The extruded feedstocks were saccharified varying the biocatalysis time and solids loading. The best conditions were 20% solids loading and 72 h of enzymatic treatment. These particular conditions converted 70% of the total fibrous carbohydrates into total fermentable C5 and C6 sugars. The extruded enzymatically hydrolyzed sweet sorghum bagasse was fermented with the strain I. orientalis at 12% solids obtaining a yield of 198.1 mL of ethanol per kilogram of bagasse (dw).